Norway : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews economic developments in Norway during the 1990s, with an emphasis on developments in 1993 and 1994. The paper covers developments in the real economy, in the public finances, and in the monetary and exchange rate area. The private consumption in Norway remained weak through the first half of 1993 but picked up sharply during the second half of the year, as declining interest rates and rising housing prices boosted consumer confidence. Seasonally adjusted, private consumption rose by 3.5 percent between the first and second halves of 1993.